1998
DOI: 10.1016/s0033-3506(98)00257-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific patterns of factors related to fatal motor vehicle traffic crashes focus on young and elderly drivers

Abstract: This population-based study examines patterns of fatal motor vehicle traffic crashes (MVTCs) by age group (16-24, 25-64, 65+) among Canadian drivers. The Canadian Traffic Accident Information Databank (TRAID) provided information about fata MVTCs between 1984 and 1993. Distribution of risk factors was compared by age group. Crude odds ratios and 95% CIs were calculated for both young and elderly drivers compared with middle-aged drivers. The middle-age group was selected as reference population since it demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 0 publications
2
44
1
3
Order By: Relevance
“…Although one prior study has suggested that younger drivers killed in crashes are more likely than drivers of other ages to have been driving in a risky manner (Zhang et al, 1998), we did not find any previously published research suggesting that the effect of risky driving differed by age. This finding is therefore a potentially important contribution of the current study and may have significant implications.…”
Section: Discussioncontrasting
confidence: 99%
“…Although one prior study has suggested that younger drivers killed in crashes are more likely than drivers of other ages to have been driving in a risky manner (Zhang et al, 1998), we did not find any previously published research suggesting that the effect of risky driving differed by age. This finding is therefore a potentially important contribution of the current study and may have significant implications.…”
Section: Discussioncontrasting
confidence: 99%
“…Although part of this excess may be an artifact, it should be recalled that we restricted our analysis to collisions, a type of crash in which the effect of alcohol may be weaker than in single crashes, as previous studies have found (19,35,36). Furthermore, alcohol consumption is more influential in younger drivers (29), and it is generally recognized that younger drivers tend to be more frequently involved in single-vehicle crashes, whereas older drivers are involved more frequently in collisions between two or more vehicles (29,35,37). In any case, the high OR estimate obtained for sleepiness/ drowsiness supports the increasing importance given to this factor in recent years as an immediate cause of traffic crashes (33,(38)(39)(40).…”
Section: Factors Directly Related With Collisionsmentioning
confidence: 95%
“…Assuming that these infractions are especially frequent among younger male drivers (29)(30)(31), this raises the possibility that we might have underestimated the cases in which these drivers were responsible for the collision. We based our decision on the fact that the DGT database considers speed infractions separately from other infractions.…”
Section: Analysis Of Speed-related Infractionsmentioning
confidence: 99%
“…These situations are well documented in the literature. For instance, older drivers are over-represented in crashes occurring while turning off at intersections, where typically the older driver turns against oncoming traffic with right of way on the main road (Hakamies-Blomqvist, 1993;Zhang et al, 1998), gap acceptance while turning left at an intersection (Langford and Koppel, 2006;Yan et al, 2007) and response to signs, signals and road hazards (Bao and Boyle, 2008;Horswill et al, 2010). A detailed description of the driving scenario is mentioned in Cuenen et al (submitted).…”
Section: Scenariomentioning
confidence: 99%